Innovative Strategies and Competitive Dynamics in Non-Profit Sports Clubs: From Transformation to Performance - García-Fernández, Jerónimo; Karimi, Javad; Pashaie, Sajjad; Golmohammadi, Hamed; Piątkowska, Monika (International Journal of Sport Studies for Health, 2025)
Objective: This paper examines the impact of IB, ED, and CA on OP in NPSOs. Given the increasing challenges such as economic and social changes and increasing competition, the present study identifies factors that can help improve the performance of these clubs.Methods and Materials: In this research, we have proposed a theoretical model and empirically tested the model in a sample of 391 board members of NPSOs in Tehran province of Iran.Findings: The findings support the proposed model, and the structural equation modeling (SEM-PLS) evaluation suggests that, IB has a positive and significant effect on OP and CA acts as a mediating variable in this relationship. Also, ED also has a positive effect on OP. Overall, the findings indicate that innovation and the ability to adapt to environmental changes can significantly contribute to improving OP.Conclusion: This research adds to the richness of the sports management literature and recommends that NPSO managers focus on enhancing innovation and adaptation to environmental changes to gain sustainable CA.